Receptive and expressive language skills in children with cri-du-chat syndrome - Cornish, K.M.; Munir, F. (Journal of communication disorders, 1998)
Receptive and expressive language skills were assessed in 13 children with cri-du-chat syndrome. Two patterns of performance were found. One pattern was the discrepancy between the children’s chronological ages and their presumed language ages. The second pattern was the receptive–expressive discrepancy with reduced expressive skills compared to receptive skills. One implication of these findings is that remediation that focuses on receptive skills may be more effective than traditional verbal methods.